PEMBATALAN SERTIFIKAT HAK MILIK ATAS TANAH ATAS PUTUSAN PENGADILAN - NI LUH ARININGSIH SARI (Universitas Mahasaraswati Mataram, 2020)
Based on the controlling rights of the State, the state in this case is the government can give land rights to someone, several people jointly or a legal entity. In the case of a human or legal entity relationship with the land gives rise to private rights for humans or the legal entity itself, and is covered by civil law. Whereas the relationship between the State and land gives birth to the State's public authority to regulate (relegate), administer (bestuuren), and control (toezichthouden) the private rights of the human or legal entity, and the study is covered by the scope of public law, the State in matters This is not a privatirechtelijk eigenaar, but has a publiekrechtelijk nature. In order to have legal certainty and to find out the individual, community group or legal entity responsible for tax payments (Building and Land Tax / Land Tax), land registration is carried out so that the owner holds proof of ownership in the form of ownership. Land Book / Land Deed prepared by an authorized official, commonly referred to as a Land Certificate. The factors that cause the cancellation of land rights are due to administrative defects, namely: Errors in Procedure; Errors in Application of Laws and Regulations; Mistakes of subject rights; Error of right object; Errors of rights types; Erroneous calculation of errors There are overlapping land rights; Juridical data or physical data that is not true; Other errors that are administrative law. And for the Court's Decision. The National Narcotics Agency has the responsibility to issue a decision on the cancellation of land rights, either because of administrative disabilities or court decisions. The process of issuing a decision on cancellation of land rights for cancellation of land rights due to administrative disability is not required there is a letter of request for cancellation, but for a decision on the cancellation of land rights due to a court decision, there must be an application from the interested parties.